2018
DOI: 10.1002/ajim.22917
|View full text |Cite
|
Sign up to set email alerts
|

Workers' compensation injury claims among workers in the private ambulance services industry—Ohio, 2001–2011

Abstract: Background Ambulance service workers frequently transfer and transport patients. These tasks involve occupational injury risks such as heavy lifting, awkward postures, and frequent motor vehicle travel. Methods We examined Ohio workers’ compensation injury claims among state‐insured ambulance service workers working for private employers from 2001 to 2011. Injury claim counts and rates are presented by claim types, diagnoses, and injury events; only counts are available by worker characteristics. Results We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The total costs associated with MVAs for HHN/HHNAs were 3.2 times that of either the combined HN/HNA or LTN/LTNA groups ($1.3 million vs. $400,000). Another occupation that has seen similar percentages for compensation claims for MVAs was private ambulance drivers (12.3% of all claims) 27 . Recent research 10–12 into the perceived hazards of HHNs and nursing aides identified several unique exposures: (1) secondhand smoke, (2) exposure to pets (e.g., animal bites and trip hazards), (3) pests (e.g., bed bugs and cockroaches), (4) egress/ingress homes multiple times a day, (5) driving motor vehicles, and (6) handling patients with no equipment.…”
Section: Discussionmentioning
confidence: 95%
“…The total costs associated with MVAs for HHN/HHNAs were 3.2 times that of either the combined HN/HNA or LTN/LTNA groups ($1.3 million vs. $400,000). Another occupation that has seen similar percentages for compensation claims for MVAs was private ambulance drivers (12.3% of all claims) 27 . Recent research 10–12 into the perceived hazards of HHNs and nursing aides identified several unique exposures: (1) secondhand smoke, (2) exposure to pets (e.g., animal bites and trip hazards), (3) pests (e.g., bed bugs and cockroaches), (4) egress/ingress homes multiple times a day, (5) driving motor vehicles, and (6) handling patients with no equipment.…”
Section: Discussionmentioning
confidence: 95%
“…Several previous research efforts focusing on particular states and specific occupations have used WC systems data to estimate the prevalence of different types of workplace injuries and the characteristics of affected workers. For example, a 10 year-long study [ 19 ] conducted among workers in the private ambulance services industry in Ohio found that around 54% of the claimants were males, and the majority (40%) were in the 25–34-year-old age-group. Around 60% of the claims were attributed to sprains and strains combined.…”
Section: Discussionmentioning
confidence: 99%
“…The research findings reveal a significant decline in the frequency of LT, MO, and total claims among LEOs, which is consistent with other OHBWC-based studies of first responders such as firefighters and ambulance service workers. 27,28 The observed decreasing trend among LEOs is also likely indicative of an overall decline in claim counts and rates within the OHBWC database. 25,29 A similar decline in occupational injury counts and rates over time has also been noted using national data sources including the BLS SOII data.…”
Section: Demographic Characteristics Of Ohio Leo Wc Claims By Injury ...mentioning
confidence: 97%